Against All Odds: How A Government’s Open Source Software (OSS) Implementation Survived - Bahri, Shamshul; Jaafar, Noor Ismawati (ACIS, 2014)
In this study, we suggest factors that influence the survival of a government’s open source software (OSS) project. Specifically, we investigated the OSS implementation by the Malaysian government since 2002. The odds were stacked against the implementation when there was a change of leadership, strong pressure from the proprietary software vendors and the less-than-stellar track record of large-scale information technology implementation such as this. The theoretical lens of this study was the Actor-Network Theory (ANT) while the method used to identify the factors that influence the survival of the OSS project was the case study research. Our findings suggest that the survival of the project was strongly influenced by the network built by its human and non-human actors that led to the successful enrolment and translation of the implementation.